Hereditary breast cancer: translation into clinical practice of recent American Society of Clinical Oncology, American Society of Radiation Oncology, and Society of Surgical Oncology recommendations. Issue 4 (3rd September 2020) - Corso, Giovanni; Magnoni, Francesca
Abstract : Scientific acquisitions concerning the risk of breast cancer in the context of hereditary breast cancer syndrome are constantly evolving: alongside the BRCA1 and BRCA2 mutations, further ones have been identified, also associated with malignancies in different sites. Therefore, management of these clinical conditions requires a multidisciplinary and shared approach, based on constantly updated guidelines. The recent Expert Panel Consensus about management of hereditary breast cancer, chaired by the Society of Surgical Oncology with the American Society of Clinical Oncology and the American Society of Radiation Oncology, based on the evidences obtained by a systematic review of the literature, delineate accurate and novel directions towards an appropriate surgical, radiation, and systemic therapy management of breast cancer patients with specific germline mutations. These recent recommendations will provide to physicians an updated and useful tool in treatment decision making of these patients in daily practice.